New Evidence of Cultural Development in Luristan in the Late Second and Early First Millennia - Goff, Clare
Ph.D.; Supervisors: S. Lloyd, A. Mellaart, B. Parker; Einteilung der Arbeit: I. The Province of Luristan; II. The Late Third and Early Second Millennia in Luristan; III. The Late Second Millennium in Luristan; IV. The Distribution of the Bronze Age Cultures and their Historical Background; V. The First Millennium in Luristan; VI. External Relations and Dating; VII. Burial Customs and Tomb Types; VIII. The Luristan Bronzes; IX. The History of First Millennium Luristan (The Cimmerians, Scythians, Persians. Ellipi, Ḫarḫar, the Medes and Kassites.